Feasibility and Safety of ERCP in the Treatment of Biliary Strictures after Liver Transplantation: With a Report of 37 Cases - Fanfan Tang; Jingtao Song; Tanxing Cai; Zhao Lei; Feizhou Huang; Yina Hu; Gang Deng (Gastroenterology Research and Practice)
Background. Liver transplantation (LT) is an effective treatment option for patients with end-stage liver disease; biliary complications are important cause of death in posttransplant patients. Endoscopic retrograde cholangiopancreatography (ERCP) has an irreplaceable role in the diagnosis and treatment of patients with biliary tract disease. Methods. The clinical data of patients with biliary strictures (BS) after LT treated with ERCP admitted to the Third Xiangya Hospital of Central South University from September 2016 to October 2021 were reviewed; the changes in temperature, bilirubin, and albumin before and after treatment and postoperative complications were analyzed. Results. A total of 41 patients were included in the study, and biliary stents were successfully placed in 37 cases (90.2%), while 4 cases (9.8%) were unsuccessful due to complete BS. Patients with ERCP guided biliary stenting had a significant improvement in bilirubin index compared to the preoperative period (P<0.05). 27 patients (73.0%) had complete relief of symptoms after 1 ERCP-guided treatment, and 10 patients (27.0%) developed BS again at different times after the first ERCP treatment, among which 8 patients developed BS again within 1 year after the first treatment and 2 patients developed BS again after 1 year after the first treatment. The incidence of endoscopy-related adverse events was 35.14%, with no serious adverse events. Conclusion. ERCP-guided biliary stenting was an effective and safety treatment for BS after LT.